(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Arundhati Roy’s The God of Small Things is apolysemic novel which can be interpreted at several levels. It may be said thatthe novel is a satire on politics attacking specifically the Communistestablishment. It may be treated as a family saga narrating the story of fourgenerations of a Christian family. It may also be treated as a novel havingreligious overtones: One may also call it a protest novel which is subversiveand taboo-breaking.